Change Strategies. (Emerald Group Pub., 2004)
How can you change a corporate mindset? How easy, or difficult, is it to get everybody reading from the same page? According to the Executives Online Group, change initiatives cost UK companies £52 billion ($96 billion) in terms of management time each year. This clearly demonstrates the significant challenge change represents for companies all over the globe. The study - available at http://www.changemanagementonline.co.uk - also reveals that 35 percent of all directors' time is devoted to change. With such widespread change occurring, handling all of the various issues that arise becomes a top priority for a manager - keeping pace with the rate of change is fast becoming a modern management necessity. If a change program is not handled appropriately - despite the best of intentions - an organization is unlikely to achieve any of its desired goals or objectives. One of the keys to successful change management lies in understanding the potential effects of a change initiative. Will employees be scared, resistant, pessimistic or enthusiastic about your proposed changes? How can each possible reaction be anticipated and managed? This Briefing aims to bring you the answers, quickly.